Sharia in Africa today : reactions and responses - Chesworth, John (John A.); Kogelmann, Franz (Leiden, The Netherlands : Brill, 2014)
Sharia in Africa Today. Reactions and Responses' explores how Islamic law has influenced relations between Muslims and Christians, through a series of case studies by young African scholars working in Sudan, Nigeria, Kenya and Tanzania
Includes bibliographical references (pages 259-269) and index
Keywords: Islamic law -- Africa; Islamic courts -- Africa